Initiating Preventive Legal Protection for Defaulted Insurance Customers: an Axiological Study - Purnomo, Hendro; Sumadi, I Putu Sudarma; Marwanto, Marwanto; Resen, Made Gde Subha Karma (East Asian Journal of Multidisciplinary Research, 2024)
Insurance helps individuals manage risks in areas like health, education, and retirement. However, issues such as defaults by insurance companies can harm customers and erode public trust. To address this, preventive measures, including establishing a Policy Guarantee Agency, are needed to protect customers and minimize losses. This normative legal study examines preventive protection regulations, focusing on balance in contracts and legal protection theories, and proposes constructing regulations for a policy guarantee program. Findings reveal that while the Insurance Law mandates such regulation, its absence creates legal uncertainty, leaving customers vulnerable to losses from insurance defaults.